Clothed in Integrity : Weaving Just Cultural Relations and the Garment Industry - Paleczny, Barbara (Studies in women and religion (Waterloo, Ont.), 2000)
Barbara Paleczny, herself a daughter of garment workers, tugs at the threads of homeworking in the garment industry to reveal a low-wage strategy that rends the fabric of social integrity and exposes global trends. The resurgence of sweatshops affects the working poor in both first- and third-world countries. Paleczny assesses the responsibility of transnational retailers for unacceptable wages and working conditions and describes historic shifts in the global context of garment production. After exploring systemic causes of poverty, relevant policy setting, and ethical foundations, Paleczny introduces both short- and long-range possibilities for transformation, emphasizing the collaborative nature of work. Clothed in Integrity draws on feminist studies, alternative economics, and the ethical foundations proposed by Bernard Lonergan to fashion a constructive work in which Paleczny connects issues of societal meanings and values, moral imperatives, and economic feasibility. With candour, she shares personal stories of engagement in coalition work. Those who dwell on this text will find information, challenges, and inspiration to nurture their reflection, research, dialogue, and action.